Cost-effectiveness analysis of alternative infant and neonatal rotavirus vaccination schedules in Malawi. - Catherine Wenger; Ernest O Asare; Jiye Kwon; Xiao Li; Edson Mwinjiwa; Jobiba Chinkhumba; Khuzwayo C Jere; Daniel Hungerford; Nigel A Cunliffe; A David Paltiel; Virginia E Pitzer (PLOS Global Public Health)
Rotavirus is the leading cause of severe diarrhea among children under five worldwide, especially in low- and middle-income countries (LMICs). Although vaccination is the best strategy to prevent rotavirus, obstacles leading to poor vaccine effectiveness undermine its impact in LMICs. This study aimed to identify the optimal rotavirus vaccination strategy for Malawi by modeling vaccine impact and cost-effectiveness, comparing the current two-dose Rotarix vaccine schedule to two alternative vaccine delivery schedules and a next-generation neonatal vaccine (RV3-BB) from 2025-2034. The cost-effectiveness of rotavirus vaccine strategies in Malawi was evaluated from the government and societal perspectives using estimates of moderate-to-severe and non-severe rotavirus cases derived from a transmission dynamic model of rotavirus and published estimates of health-seeking behaviors and costs as inputs. A probabilistic sensitivity analysis was performed to evaluate the robustness of our results to parameter uncertainty. Over a ten-year time horizon, the current two-dose Rotarix strategy is predicted to avert over 1.5 million cases and 90,000 disability-adjusted life-years (DALYs) compared to no vaccination and is cost-effective at willingness-to-pay (WTP) thresholds above $105 per DALY averted from the government perspective. Adding a third dose at 14 weeks could avert an additional 1 million cases and 38,000 DALYs, while switching to the neonatal RV3-BB vaccine could avert 1.1 million cases and 41,000 DALYs compared to the current strategy. Whereas adding a third dose of Rotarix would cost $4.1-4.9 million, switching to the neonatal vaccine is expected to save $3.7 million compared to the current strategy. Considering the neonatal vaccine is not yet available, adding a third dose of Rotarix at 14 weeks of age is cost-effective at WTP thresholds above $138 per DALY averted. The neonatal vaccine offers a more cost-effective alternative to Malawi's current rotavirus vaccine, while adding a third dose to the current strategy also provides substantial benefits.